Strategies for developing multi-epitope, subunit-based, chemically synthesized anti-malarial vaccines (2008)
Introduction•P. falciparum invasion of RBCs•Merozoite proteins involved in invading erythrocytes•Erythrocyte proteins involved in merozoite invasionThe state of current worldwide anti?malarial vaccine approaches • A rational approach towards developing subunit?based synthetic vaccines • The immune response elicited by conserved HABPs • Structural analysis of native and modified HABPs • Secondary structure analysis • Native and modified HABP 3D structure explains some immunological phenomena • Supporting the haplotype – and allele?conscious TCR concept • Modified HABPs' 3D structure revealed a fit into HLA molecules • Conclusion Abstract An anti?malarial vaccine against the extremely lethal Plasmodium falciparum is desperately needed. Peptides from this parasite's proteins involved in invasion and having high red blood cell?binding ability were identified; these conserved peptides were not immun genic or protection?inducing when used for immunizing Aotus monkeys. Modifying some critical binding residues in these high?activi binding peptides' (HABPs') attachment to red blood cells (RBC) allowed them to induce immunogenicity and protection against expermental challenge and acquire the ability to bind to specific HLA?DRp1* alleles. These modified HABPs adopted certain characterist structural configurations as determined by circular dichroism (CD) and 1H nuclear magnetic resonance (NMR) associated with certain HLA?DR?1* haplotype binding activities and characteristics, such as a 2?Å?distance difference between amino acids fitting into HLA?DRp1 Pockets 1 to 9, residues participating in binding to HLA?DR pockets and residues making contact with the TCR, suggesting haplotyp and allele?conscious TCR. This has been demonstrated in HLA?DR?like genotyped monkeys and provides the basis for designing high effective, subunit?based, multi?antigen, multi?stage, synthetic vaccines, for immediate human use, malaria being one of them.